Redefinition of Physciolagria Pic, 1930 (Coleoptera: Mycteridae) with a new family placement, genus-rank synonymy, new description, and a key - Telnov, Dmitry (Zootaxa, 2022)
Physciolagria Pic, 1930, a monotypic genus erroneously attributed to Tenebrionidae incertae sedis was found to be congeneric with the eurypine genus Lacconotopedilus Pic, 1935 (Mycteridae Blanchard, 1845). The taxonomic position and comparative morphology of Physciolagria are reassessed and discussed. A new genus-rank synonym (Physciolagria Pic, 1930 = Lacconotopedilus Pic, 1935 syn. nov.), one species-rank synonym (Physciolagria liturata Pic, 1930 = Lacconotopedilus elongatus Pic, 1936 syn. nov.) and two new combinations are proposed. Physciolagria smithi sp. nov. from Senegal is described and P. liturata and P. singularicornis are redescribed and illustrated. An annotated checklist, key to species and new records are provided.